Analisis Pemanfaatan Limbah Rumah Tangga sebagai Sumber Energi Alternatif - Sabran F Harun; Saharuddin Ronge Sokku (Seminar Nasional LP2M UNM, 2019)
Utilization of waste into alternative energy is still very minimal, only around 1600 MW or around 3.25% of the existing potential. Several small-scale biogas installations have been held. However, the installation is still limited to sources from palm oil waste and livestock manure, while household waste has not been managed optimally. The volume of waste in Indonesia is around 64 million tons per year. Until 2020, the volume of urban waste is expected to increase five times. Meanwhile, it is estimated that from the process of planting, production, shipping to final consumption, more than 40% of food becomes junk. This becomes a big problem if it is not handled properly, even though waste saves a large energy potential